2009
DOI: 10.2164/jandrol.108.006940
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Supplementation Does Not Affect Testicular Selenium Status or Semen Quality in North American Men

Abstract: Selenium (Se) is essential for sperm function and male fertility, but high Se intake has been associated with impaired semen quality. We reported previously a decrease in sperm motility in men fed high-Se foods, but we could not rule out the influence of other environmental and dietary factors. We now report on a randomized, controlled study on the potential adverse effects of Se supplementation on semen quality in 42 free-living men administered Se (300 mg/d) as high-Se yeast for 48 weeks. Semen analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 50 publications
(49 reference statements)
2
37
1
Order By: Relevance
“…Of the 23 included studies, 7 (n ¼ 1084 patients) evaluated the effect of dietary habits and food intake on semen parameters and quality, 2,25,28,48 4 (n ¼ 232 patients) evaluated the effect of carnitine consumption on sperm parameters and quality, 54-57 3 (n ¼ 148 patients) investigated the effect of selenium on sperm parameters, 58-60 2 (n ¼ 481 patients) evaluated the effect of coenzyme Q10 on sperm quality and parameters, 61,62 and each of the remaining articles investigated the effect of saffron, soybased foods, vitamin C, clomiphene citrate, n-3 polyunsaturated fatty acids, beta carotene, and ubiquinol on sperm parameters. [63][64][65][66][67][68][69] The 23 articles included patients from 9 different countries: Iran (6 articles), 2,[61][62][63]67,69 the United States (7 articles), 28,54,58,64,[70][71][72] Italy (3 articles), [55][56][57] Egypt (2 articles), 66,68 the United Kingdom (1 article), 60 Germany (1 article), 65 Poland (1 article), 59 Spain (1 article), 48 and Brazil (1 article). 25 …”
Section: Overview Of Identified Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 23 included studies, 7 (n ¼ 1084 patients) evaluated the effect of dietary habits and food intake on semen parameters and quality, 2,25,28,48 4 (n ¼ 232 patients) evaluated the effect of carnitine consumption on sperm parameters and quality, 54-57 3 (n ¼ 148 patients) investigated the effect of selenium on sperm parameters, 58-60 2 (n ¼ 481 patients) evaluated the effect of coenzyme Q10 on sperm quality and parameters, 61,62 and each of the remaining articles investigated the effect of saffron, soybased foods, vitamin C, clomiphene citrate, n-3 polyunsaturated fatty acids, beta carotene, and ubiquinol on sperm parameters. [63][64][65][66][67][68][69] The 23 articles included patients from 9 different countries: Iran (6 articles), 2,[61][62][63]67,69 the United States (7 articles), 28,54,58,64,[70][71][72] Italy (3 articles), [55][56][57] Egypt (2 articles), 66,68 the United Kingdom (1 article), 60 Germany (1 article), 65 Poland (1 article), 59 Spain (1 article), 48 and Brazil (1 article). 25 …”
Section: Overview Of Identified Studiesmentioning
confidence: 99%
“…The single agents were saffron, 63 coenzyme Q10, 61,62,69 and selenium. 58,59 The average duration of the studies was 24 weeks.…”
Section: Interventions or Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…47,[50][51][52][53][54][55] Three RCTs evaluated the effects of selenium alone or in combination with N-acetyl cysteine and two of the three studies reported a significant improvement in sperm parameters in the treatment arm only. 43,48,54 Four RCTs evaluated the effects of L-carnitine alone or in combination with L-acetyl carnitine and three of the four reported a significant improvement in sperm parameters in the treatment arm only. 42,44,49,60 Three RCTs evaluated the effects of N-acetyl cysteine alone or in combination with selenium and all three reported a significant improvement in sperm parameters in the treatment arm only.…”
Section: Relationship Between Oxidative Stress and Sperm Dysfunctionmentioning
confidence: 99%